Analysis of the welfare level of fish farming groups in Sebulu Ulu Village, Sebulu District, Kutai Kartanegara Regency - Ihsan, Aji Muhammad Ridho; Syafril , Muhammad; Fahrizal, Wahyu (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Economic development is the process of increasing overall income and per capita income while considering population growth and maximizing welfare for the benefit of families and communities. This study aims to analyze the welfare level of fish farming groups using indicators from the Central Bureau of Statistics (BPS) and the Fish Farmers' Exchange Rate (NTPi). The required data consists of both primary and secondary data in accordance with the research objectives. The research findings indicate that fish farmers in Sebulu Ulu Village, Sebulu District, Kutai Kartanegara Regency, are categorized as prosperous. Based on the 2016 BPS welfare indicators, the average score obtained was 19, with 6 respondents (60%) classified as having a moderate level of household welfare, meaning that their living conditions are fairly prosperous. According to the NTPi indicator, the total income of fishing families was 1.23, while the total income of fish farming businesses was 1.96. Since these values are greater than 1, it indicates that the majority of fish farming families are already prosperous.